Doxycycline prophylaxis for bacterial sexually transmitted infections: evaluating effectiveness, risks, and challenges - Filipe Monteiro; João Borges- (Sociedade Portuguesa de Dermatologia e Venereologia, 2024)
The increase in sexually transmitted infections (STIs) in Europe and the USA, especially among men who have sex with men (MSM) and transgender women (TW), has raised concerns and prompted the exploration of doxycycline prophylaxis as a potential intervention. Doxycycline prophylaxis can be administered either as a daily 100 mg dose (DoxyPrEP) or a single 200 mg dose post-sexual activity (DoxyPEP). Recent clinical trials, primarily focusing on higher-risk groups, have shown reductions of approximately 70% in syphilis and chlamydia infections and conflicting results regarding gonorrhea infection (up to 50%). Despite these advancements, the effectiveness of doxycycline prophylaxis among women has not been established and this strategy raises concerns about community acceptability, adverse events, safety, antimicrobial resistance, microbiome disruption, and cost-effectiveness. Ongoing clinical trials and agent-based models aim to address these uncertainties to predict the impact on a population level and on specific groups. This review aims to assess the existing data of doxycycline STI prophylaxis, identify knowledge gaps, and synthesize existing literature and guidelines about the current recommendations.